An analysis of male humour on Malaysian radio / Nooralida Mohd Noor - Nooralida , Mohd Noor (2015)
Some Malaysian radio hosts integrate humour in their shows. Using Content Analysis, this study investigates three areas of conversational humour on a Malaysian radio show: (1) the humour techniques present in the selected episodes; (2) the linguistic characteristics these humour techniques have; and (3) the humour functions these techniques serve. It centres on investigating humour found in the interactions of two male radio hosts and the listeners in a Malaysian radio breakfast show. The theoretical frameworks of Hay’s Humour Types Taxonomy, Mihalcea and Strapparava's Verbal Humour Linguistics Characteristics, and Hay’s Functions of Humour Taxonomy are used to analyse the data. The results indicate that for the humour techniques, observational humour (i.e. funny remarks based on observation of a current situation, or a previous person’s words) is found to be the most frequent technique used, followed by ridicule. The most frequently used linguistic characteristic of verbal humour is human-centered vocabulary (i.e. words describing human beings, social relations, and social groups), followed by negative orientation (i.e. words that have a negative load or negative connotations). In the categories of humour functions, general function (i.e. creating a positive self-identity) has the highest frequency, while solidarity function (i.e. establishing a sense of belonging between group members) has the second highest frequency. 14 humour techniques and 4 humour functions were found in the data. The humour also uses 4 of the 5 semantic categories of the linguistic characteristics of verbal humour. It is hoped the findings of this study are able to contribute to the pool of knowledge on humour in male speech in Malaysian setting.